Perbandingan Perhitungan Volume Batubara Stock Rom Mengunakan Hasil Pengukuran Total Station dan Unmanned Aerial Vehicle di PT Victor Dua Tiga - Adit Ajie Nugraha; Lucia Litha Respati; Windhu Nugroho; Henny Magdalena; Agus Winarno (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Measuring coal volume in the Stock ROM area played an important role in production control and mining evaluation. This research was conducted in the Stock ROM area at PT. Victor Dua Tiga Mega, where volume measurements were generally carried out using Total Station (TS) as the main method, howefer the use of Unmanned Aerial Vehicles (UAV) has begun to be implemented as a more efficient alternative. This study aims to compare the results of Stock ROM coal volume calculations using the Total Station and UAV methods. The research method was carried out by collecting data in the field, processing the digital Elevation Model (DEM), and calculating the volume using the Cut and Fill method. The results of the study the difference in volume between the two methods, where the UAV measurement results tend to be greater than those of the Total Station. The difference in Fine Coal volume was 724,15 m3 or 16,74% and Raw Coal volume of 9.335,98 m3 or 8,03%. Based on a comparison with weighing data, measurements using the Total Station provided results that were closer to the actual conditions in the field.